A theoretical analysis of public procurement for innovation - Sunjoo Hwang (KDI Journal of Economic Policy, 2024)
This paper provides a new theoretical rationale for public procurement for innovation (PPI), a unique policy encouraging public procurers to purchase innovative products. In contrast to existing studies that primarily emphasize the advantages of PPI, this paper takes a comprehensive approach, examining both the costs and risks associated with PPI, alongside its benefits. It finds a general condition under which PPI outperforms traditional public procurement. Under this condition, this paper demonstrates that PPI enhances social welfare by facilitating optimal risk-sharing between public procurers and the general economy. Additionally, it draws policy implications from a comparative analysis between the current PPI policy in Korea and an optimal PPI policy.
Keywords: D86; H57; O38; 330; Public Procurement for Innovation; Optimal Risk Sharing; State-Owned Enterprises